2007
DOI: 10.1002/chem.200601033
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthetic Route to 2 H‐Chromenes: Reconsideration of the Mechanism of the DBU‐Catalyzed Reaction between Salicylic Aldehydes and Ethyl 2‐Methylbuta‐2,3‐dienoate

Abstract: Reactions of salicylaldehydes with ethyl buta-2,3-dienoate or penta-3,4-dien-2-one catalyzed by a catalytic amount of potassium carbonate produce the corresponding 2 H-chromene products in moderate to good yields under mild conditions. A plausible reaction mechanism is discussed in the light of the results of an 18O-labeling experiment. In addition, in view of these findings, the catalytic function of DBU in reactions of this kind is reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…When LS-Sc II, which possesses a lower Sc loading than that of LS-Sc I, was used in the reaction, only a moderate yield was obtained under the identical conditions (entry 10), which implied the fact that scandium loading on the NaLS support was also able to significantly affect the catalytic activity of the prepared lignin-immobilized metal catalyst. The effect of the organic solvents on the model reaction was also examined, in which ethanol and acetonitrile gave high yields (entries [11][12][13][14][15]. For safety and environmental reasons, we continued the reactions with ethanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When LS-Sc II, which possesses a lower Sc loading than that of LS-Sc I, was used in the reaction, only a moderate yield was obtained under the identical conditions (entry 10), which implied the fact that scandium loading on the NaLS support was also able to significantly affect the catalytic activity of the prepared lignin-immobilized metal catalyst. The effect of the organic solvents on the model reaction was also examined, in which ethanol and acetonitrile gave high yields (entries [11][12][13][14][15]. For safety and environmental reasons, we continued the reactions with ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…In the beginning, we undertook this study with the implementation of a Michael addition/dehydration tandem reaction of 3‐acetyl‐2‐hydroxy‐2‐methylchromene and indole that might be able to provide densely functionalized 4 H ‐chromene derivatives, which have showed various interesting pharmacological properties 13. Although 3‐acetyl‐2‐hydroxy‐2‐methylchromene could be easily obtained through condensation of salicylaldehyde and acetoacetone,14 its use as a Michael acceptor has not been evaluated before. In continuation of our research to synthesize substituted 4 H ‐chromenes,15 we envisioned that Michael addition/dehydration tandem reaction of 3‐acetyl‐2‐hydroxy‐2‐methylchromene with a nucleophile should be a possible way for constructing these heterocycles.…”
Section: Resultsmentioning
confidence: 99%
“…After that, we found that yields were affected by the loading of the PS-PTSA catalyst. When 5, 10, 20, and 30 mol% of PS-PTSA were used, the yields were 85, 98, 98, and 96 % respectively (Table 2, entries 10,11,12,13). Therefore, 10 mol% of PS-PTSA was chosen as the ideal catalytic amount for the model reaction noting that using additional amount of the catalyst did not increase the yield nor decrease the reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, considerable effort has been invested in the synthesis of indolyl 4H -chromene derivatives using L-proline and an aqueous micellar system for the reaction between salicylic aldehyde, dimedone, and indole [10]; tetrahydrothiophenecatalyzed ylide annulation reaction (E)-ethyl 4-(2-(bromome thyl)phenyl) but-2-enoate gave 4H -chromene [11]; DBUcatalyzed reaction between salicylic aldehydes and ethyl 2-methylbuta-2,3-dienoate [12]; tandem benzylation and cyclization catalyzed by FeCl 3 [13]; Cu(I)-catalyzed domino reactions [14]; and triazine-functionalized ordered mesoporous organosilica as an organocatalyst [15]. A survey of the literature shows that the majority of the strategies for the synthesis of 4H -chromene derivatives involve multistep reaction sequences [11,16], prolonged reaction times, harsh reaction conditions [13,17,18], tedious work-up procedure [19], and some procedures failed to recover and reuse the catalyst [20][21][22][23][24].…”
mentioning
confidence: 99%
“…In the recent years, they have been used in sensors for detection of metals and some compounds with high selectivity 9,10 . Until now, diverse methods have been published for the synthesis of 2H-benzopyran derivatives [11][12][13][14][15][16][17] . They are also good intermediates that have been applied in several organic synthesis [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%